The Faktor – Faktor Yang Berhubungan Dengan Kepuasan Pasien Terhadap Pelayanan Keperawatan di Ruang Rawat Inap Rumah Sakit Panti Rapih Yogyakarta - Purwantiningsih, Emiliana Hesti; Oktri Hastuti, Agustina Sri; Mahayanti, Agnes (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background : Patient satisfaction is the feeling that is felt and expressed by the patient after comparing expectations with expectations after getting service. Quality care gives patients permission to have a strong relationship with the hospital. Patient satisfaction ultimately affects patient loyalty to a hospital that provides satisfactory quality Objective : Knowing the factors that are related to satisfaction with nursing services in the inpatient room of the hospital, Yogyakarta neat nursing. Methods : The research design used was a correlation study using a cross sectional approach. Taking sampling using purposive sampling. The population in this study were patients who were hospitalized in the neat nursing home room Carolus 5, Elisabet 1 and Elisabet 4, a sample of 188 respondents. Data collection used a questionnaire measuring tool, then the data were analyzed using the Spearman'rho statistical test. Results : There is a significant relationship between facilities, performance, service, atmosphere and communication factors with patient satisfaction with p value = 0.000 Conculsion : There is a significant relationship between facilities, performance, service, atmosphere and communication factors with patient satisfaction with p value = 0.000 Suggestion: For the Head of Hospital: make plans for monitoring the implementation of SOPs regularly, for employees about nursing actions, so that patients feel the professional performance of nurses, for implementing nurses: Implementing nurses apply SOPs for every nursing action correctly, at pre interactive specifically in introductory communication, it is important that nurses introduce themselves, provided provisioning excellent service to new employees. For the College of Health Sciences, Panti Rapih, the factors related to patient satisfaction have not all been examined, the results of this study can be used as initial data to conduct research further, with other methods and more respondents Key words : Facilities, services, performance, communication, atmosphere, patient satisfaction